2008
DOI: 10.4141/cjas07075
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and ruminal degradability of grain pearl millet grown in southwestern Quebec

Abstract: . 2008. Chemical composition and ruminal degradability of grain pearl millet grown in southwestern Quebec. Can. J. Anim. Sci. 88: 71Á77. The objectives of this study were to determine the chemical composition and ruminal nutrient degradabilities of grain of five hybrids of pearl millet grown in southwestern Quebec. Hybrids were selected because they were poor hosts of the widely prevalent root lesion nematode (Pratylenchus penetrans). Neutral detergent fiber and acid detergent lignin were similar for all hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
2
8
1
Order By: Relevance
“…While crude protein and oil contents in this study are lower than that reported for some pearl millet hybrids in Canada [32], protein content are within the range 88 -209 g•kg −1 previously reported for pearl millet [33]. TifGrain 102 millet has been reported before where it is indicated to have comparable total metabolizable energy (TME) and higher protein content than corn [34].…”
Section: Seed Protein and Oil Contentsupporting
confidence: 45%
“…While crude protein and oil contents in this study are lower than that reported for some pearl millet hybrids in Canada [32], protein content are within the range 88 -209 g•kg −1 previously reported for pearl millet [33]. TifGrain 102 millet has been reported before where it is indicated to have comparable total metabolizable energy (TME) and higher protein content than corn [34].…”
Section: Seed Protein and Oil Contentsupporting
confidence: 45%
“…A major constraint lies in the unavailability of a nutritionally rich PM variety that could adapt well to the harsh Canadian growing conditions and relatively short summer season. It is also worth mentioning that the concentrations of ME, CP, amino acids, and antinutritional factors vary greatly between different PM varieties (Buerkert et al, 2001;Mustafa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in agreement with other report that enzyme supplementation of corn‐based diets did not alter BW and FCR (Madrid et al., ). To the best of our knowledge, there was little study evaluating the effects of enzyme addition to pearl millet‐based diets on broiler performance, as the arabinose and xylans are the major water‐soluble NSP in PM grains (Mustafa et al., ). In this study, the only observed positive effect of enzyme supplementations on broiler performance was increased performance of birds that consumed of the PM diet compared with the CTL diet.…”
Section: Resultsmentioning
confidence: 99%
“…The investigation of sprouting of pearl millet‐based diets on broiler performance is another novel approach of this study. Arabinose and xylans are the major water‐soluble NSP in PM grains (Mustafa et al., ), and dietary inclusions of this grain necessitate enzyme supplementation or sprouting to alleviate the problems of increased viscosity, reduced nutrient utilization and depressed growth in broilers (Shirzadi et al., ). Therefore, we can assume that pearl millet‐based diets contained some insoluble NSP because of the positive effects that we observed with ES and sprouting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation